(untitled) (University of Thi-Qar Journal for Engineering Sciences, 2019)
This paper includes an experimental study of the effect of dynamical vibration (harmonic waves) or wind on the deformation of the ship hull when it is in the case of pitching motion and rolling. The aim of this paper is to calculate the strains of the ship as a result of the effect of waves on it. Aluminum alloy was used to build the frame of the model with suitable dimensions, and then fixed the model on the vibrating system which consists of number of springs with limiting stiffness. Vibrating system supported with means to generate waves with (0.75Hz, 1Hz, 1.25Hz) frequencies. The deformations are measured at the pitching and rolling motion of the model. The results showed that the strains of the model in the pitching motion greater than the rolling motion. When the frequency increases, the strains are increases